2007
DOI: 10.1111/j.1526-4610.2006.00724.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Migraine and Patent Foramen Ovale: A Study of 121 Patients with Migraine

Abstract: Our findings suggest possible association of migraine with aura and PFO. It seems that PFO does not influence the type of aura and frequency of attacks of migraine as well as it is not associated with familial occurrence of migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
47
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 57 publications
6
47
0
1
Order By: Relevance
“…Indeed, the mechanism of sudden deafness in patients with RLS remains unclear, but paradoxical embolism might provoke transient focal neurological symptoms by vasoconstriction and transient cerebral ischemia and secondary to vasospasm or cortical spreading depression, such as migraine [10]. Focusing on cerebral ischemia and acute hearing loss, the internal auditory artery (labyrinthine artery) supplies blood to both the cochlea and the vestibule.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the mechanism of sudden deafness in patients with RLS remains unclear, but paradoxical embolism might provoke transient focal neurological symptoms by vasoconstriction and transient cerebral ischemia and secondary to vasospasm or cortical spreading depression, such as migraine [10]. Focusing on cerebral ischemia and acute hearing loss, the internal auditory artery (labyrinthine artery) supplies blood to both the cochlea and the vestibule.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that individuals with migraine are more likely to have a PFO, and this association is most evident in those whose attacks of migraine may be accompanied by aura. Patent foramen ovale has a prevalence of 15-25% in the general population [11,17,25] and up to 60% in patients with migraine with aura in casecontrol studies [1,9,12,14,26]. Although the mechanism of attacks of migraine in patients with PFO is stil unclear, some studies have suggested the hypothesis of a potential association between PFO and migraine [1,9].…”
Section: Discussionmentioning
confidence: 95%
“…Control group 12/8 11.5 (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) patients with RLS tend to report Valsalva-provoking activities to trigger their headache attacks [30]. We also consider the Valsalva maneuver may suggest that opening of RLS acted as a trigger for migraine attack.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…A meta analysis of 7 studies in adult population with migraine headache and aura showed association of PFO in this particular population ranging from 41-62% (composite of 56% by meta-analysis) (23)(24)(25)(26)(27)(28)(29).…”
Section: The Association Of Migraine Headache and Patent Foramen Ovalementioning
confidence: 99%